2018
DOI: 10.15218/zjms.2018.013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of wound dressing practices among nurses at the emergency hospitals in Erbil city

Abstract: * Erbil Director of Health,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 3 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…Both articles indicate there is no association between nurses' practices and education while, on study done by Khudhair [2] show that, nurses who had pervious clinical experiences positively impact safe clinical practice regarding wound management. At the same time, other studies done by Najm [5]; El-Sayed et al [18] found different relationships that indicate there is no association between nurse's performance and their educational background and their clinical experiences.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Both articles indicate there is no association between nurses' practices and education while, on study done by Khudhair [2] show that, nurses who had pervious clinical experiences positively impact safe clinical practice regarding wound management. At the same time, other studies done by Najm [5]; El-Sayed et al [18] found different relationships that indicate there is no association between nurse's performance and their educational background and their clinical experiences.…”
Section: Discussionmentioning
confidence: 95%
“…The articles were performed in various geographical locations such as -India Dhanasundari [3]; Anjumol [8]; Margareat Thatcher [9]; Brazil Arruda et al [10]; Faria [12]; Pakistan Ghosh [12]; Bilal et al [13], Iraq Najm [5]; Jordan Saleh [14]; Sri Lanka Kumarasinghe [15], Saudi Arabia BaMohammed [2], Nigeria Ogunfowokan [16]; Turkey Asiye Gul [17]; Egypt El-Sayed [18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective wound care promotes wound healing and leads to early discharge and saving costs. The dressing protects the wound from injury, prevents introduction of bacteria, reduces discomfort, and speeds healing (5).Even to prevent such post-operative complications, it is necessary to study existing wound care practices and measure the difference between these and, ideally, to lean more towards evidence-based practices for wound care (6).…”
Section: Introductionmentioning
confidence: 99%